Means of Improving Methodological Training of Future Primary Class Teachers Using the TIMSS International Assessment Program (Eurasian Scientific Herald, 2022)
This article gives information about TIMSS international assessment program and the tools of international assessment programs in improving the methodological training of future primary school teachers.